The Effect Of Harmonious Passion, Competence, And Islamic Work Ethics On Teacher Performance With Organizational Citizenship Behavior As A Mediator At Al-Azhar Aceh Social Education and Prophecy Foundation - Aulia, Muhammad; Djalil, Muslim A; Putra, Teuku Roli Ilhamsyah (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to examine the impact of harmonious passion, competence, and Islamic work ethics on teacher performance, with organizational citizenship behavior (OCB) serving as a mediator. It focuses on the Al-Azhar Aceh Social Education and Prophecy Foundation, which operates three Islamic schools in Banda Aceh. The target population includes all teachers at the Al-Azhar schools, comprising kindergarten, elementary, and junior high school educators, totaling 154 individuals. A census technique was employed for sample selection, meaning the entire population was included as the sample. Data analysis was conducted using the Structural Equation Modeling (SEM). The findings reveal that harmonious passion, competence, and Islamic work ethics have a significant impact on OCB; furthermore, harmonious passion and competence, along with OCB, significantly affect teacher performance, though Islamic work ethics do not. Additionally, OCB mediates the effects of harmonious passion, competence, and Islamic work ethics on teacher performance.